2021
DOI: 10.1111/jopr.13408
|View full text |Cite
|
Sign up to set email alerts
|

Removable Partial Dentures with Polyetheretherketone Framework: The Influence on Residual Ridge Stability

Abstract: Purpose: To provide, in a clinical case-control study, 1-year data on edentulous residual ridge dimensional changes for patients wearing removable partial dentures (RPD) with Polyetheretherketone (PEEK) framework, fabricated with a digital workflow, and a control group of untreated patients. Materials and Methods: Ten patients were treated with PEEK RPD, and six controls were studied. Intraoral scans at baseline (T0) and after a median period of 1 year (T1) were superimposed, trimmed, and reoriented (T0r and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…The reasons for their exclusion are provided in Table 1. Therefore, 12 studies were deemed suitable for inclusion in this review [20,24,[33][34][35][36][37][38][39][40][41][42]. No additional studies were found upon hand searching, and none was found within the references of the included studies.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…The reasons for their exclusion are provided in Table 1. Therefore, 12 studies were deemed suitable for inclusion in this review [20,24,[33][34][35][36][37][38][39][40][41][42]. No additional studies were found upon hand searching, and none was found within the references of the included studies.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Eight of the included studies were case reports [20,[33][34][35][36][37][38]40], two studies were cohort studies [24,39], one study was a randomised controlled trial (RCT) [41] and another one was a case-control study [42]. Case reports documented six patients who received single PEEK prostheses [20,[33][34][35][36][37][38]40].…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations